2018
DOI: 10.1590/1678-5150-pvb-5243
|View full text |Cite
|
Sign up to set email alerts
|

Abortos, malformações congênitas e falhas reprodutivas espontâneas em caprinos causados na intoxicação pelas folhas da catingueira, Poincianella pyramidalis (sin. Caesalpinia pyramidalis)

Abstract: RESUMO: O objetivo deste estudo foi investigar os efeitos de folhas da espécie arbórea Poincianella pyramidalis (Tul.) L.P. Queiroz como causa espontânea de abortos, malformações e falhas reprodutivas em rebanhos caprinos no semiárido brasileiro. Foram realizadas investigações epidemiológicas, avaliações clínicas de caprinos acometidos por malformações e necropsias de fetos abortados em 12 propriedades localizadas nos municípios de Gurjão e Soledade, na Paraíba, e no município de Pau dos Ferros, Rio Grande do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Malformation due to ingestion of apple pomace by pregnant cows should be assessed by differential diagnosis of the malformations caused by plants. In the Northeast Region of Brazil, ingestion of "jurema preta" (Mimosa tenuiflora) and "catingueira" (Poincianella pyramidalis) leads to craniofacial osseous anomalies, ocular malformation, and arthrogryposis (Pimentel et al 2007, Medeiros et al 2008, Souza et al 2018, Dantas et al 2010, Santos et al 2012. Intoxication with Lupinus angustifolius, Veratrum californicum, Nicotiana glauca (Kellerman et al 1990), and Conium maculatum (Tokarnia et al 1985) experimentally affect not only bovines, but also ovine, swine and goats, which in addition to malformations, also present signs of salivation, staggering gait, tremors, convulsions, and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Malformation due to ingestion of apple pomace by pregnant cows should be assessed by differential diagnosis of the malformations caused by plants. In the Northeast Region of Brazil, ingestion of "jurema preta" (Mimosa tenuiflora) and "catingueira" (Poincianella pyramidalis) leads to craniofacial osseous anomalies, ocular malformation, and arthrogryposis (Pimentel et al 2007, Medeiros et al 2008, Souza et al 2018, Dantas et al 2010, Santos et al 2012. Intoxication with Lupinus angustifolius, Veratrum californicum, Nicotiana glauca (Kellerman et al 1990), and Conium maculatum (Tokarnia et al 1985) experimentally affect not only bovines, but also ovine, swine and goats, which in addition to malformations, also present signs of salivation, staggering gait, tremors, convulsions, and dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos que se dedicaram as plantas toxicas com potencial teratogênico se fez escasso nessa pesquisa quando segredados apenas os estudos de caráter observacional, sendo selecionados apenas: Silva et al (2012), no comércio informal de Goiânia, com 10 "raizeiros "mais consagrados pela população local que contatou-se no desconhecimento dos vendedores locais em relação aos perigos tóxicos e abortivos das plantas por eles indicadas para o uso por gestante e crianças; Macêdo (2015), na Universidade Federal da Paraíba, com ruminantes que possuíam malformações fetais, onde foi comprovado que a Caesalpina pyramidalis (catingueira) foi a causadora dessas malformações em diferentes regiões dos mesmos; Souza et al (2018), na Paraíba e no Rio Grande do Norte, com rebanho de caprinos que comprovaram os efeitos de folhas da espécie arbórea Poincianella pyramidalis como causa espontânea de abortos, malformações e falhas reprodutivas nesses rebanhos de caprinos.…”
Section: Desfechos Relacionados à Gravidez Em áReasunclassified
“…In the semi-arid region, where cases of natural poisoning have occurred (Marcelino et al 2017), in addition to the toxic effects on females, many small ruminant producers reported that C. pyramidale also causes reproductive problems in male sheep and goats (Souza et al 2018). Until then, reproductive changes due to consumption of C. pyramidale had only been proven in pregnant goats and sheep (Reis et al 2016, Lopes et al 2017, but toxic effects on the reproductive parameters in males had been observed.…”
Section: Introductionmentioning
confidence: 99%